Biopolymer-Coated Magnetite Nanoparticles For The Removal Of Emerging Contaminants From Aqueous Solutions - Farghal, Hebatullah (AUC Knowledge Fountain, 2023)
Abstract Biopolymers are gaining interest as promising materials for water purification due to their functionality, biodegradability, abundance, and safe use. In this work, three biopolymer-based systems were developed as adsorbents for removing emerging contaminants from water. The first system of biopolymeric nanocomposites was synthesized by coating chitosan/xylan biopolymeric nanocomposites on magnetite nanoparticles (CsXM) to facilitate their separation from water via a magnetic field. The prepared mesoporous CsXM nanocomposite was thermally stable and possessed a particle size of 11 nm and a neutral to slightly negative charge over the studied pH range of about 3 to 10. The nanocomposite efficiently removed Pb(II), salicylic acid (SA) anti-inflammatory drug and Congo Red (CR) dye with efficiencies of 64.49, 62.9, and 70.35%, respectively, on applying 6 g/L adsorbent dose at an initial concentration of 50 ppm for each contaminant. CsXM efficiently adsorbed the contaminants in ternary system where Pb(II) and (SA) were more competitive than CR. Mechanisms of binding included complexation, hydrogen bonding as well as van der Waals interactions, thus demonstrating the multifunctionality of CsXM in capturing contaminants of different charges. Biopolymers can be possible candidates for pollution at disposal and during production since the rate of their production far exceeds the need for its composting; in addition, they create methane emissions in landfills. Hence, biopolymer-derived hydrochars were investigated as the second adsorbent system in this work. Expired cellulose was hydrothermally treated to obtain a hydrochar with increased porosity and functionality capable of adsorbing the antidepressant Fluoxetine HCl (FLX) and Methylene Blue dye from water. Hydrothermal treatment provides a greener approach for synthesis than conventional pyrolysis since it is water based. The produced hydrochar showed the characteristic D and G bands in Raman spectrum and exhibited better thermal stability and BET surface area than expired and fresh cellulose. Adsorption kinetics were fast while equilibrium followed Langmuir isotherm with maximum adsorption capacity of 5 about 30 mg/g at pH 7.5 and removal efficiencies that exceeded 90% for both contaminants. Interactions between the hydrochar and the contaminants occurred mainly via electrostatic attractions, along with possible π—π stacking. Coating of the hydrochar over magnetite further increased the surface area and consequently the percent removal of both contaminants by about 30% and 13%, respectively, over the bare hydrochar. The hydrochars could be reused for four consecutive cycles. To benefit from the advantages of both biopolymers and activated carbons, the third adsorbent system was prepared by incorporating a biopolymer of xylan or pectin with activated charcoal along with magnetite. This combination enhanced the chemical and thermal stability of activated charcoal and improved its regeneration performance. The synthesis of this nanocomposite was performed using two different routes and applied on the removal of FLX and Famotidine (FAM) drugs. The one pot synthesis route provided better removal efficiency and thus was selected for further studies. The mesoporous nanocomposites that incorporated xylan adsorbed FLX and FAM with respective maximum adsorption capacities of 90.9 and 42.9 mg/g, while those incorporating pectin yielded 114.9 and 53.5 mg/g, respectively. The underlying adsorption mechanisms were hypothesized to be electrostatic attractions and hydrophobic interactions. Simultaneous adsorption of FLX and FAM in spiked tap water gave comparable results to their adsorption in distilled water indicating that adsorption was not affected by competition from other species in water. The three developed adsorbent systems are characterized by their functionality, efficiency, and eco-friendliness. Thus, they can be easily and safely utilized in water treatment systems. The work in this thesis has implications for pollution reduction, circular economy and management of natural resources which are in line with the UN Sustainable Development Goals (SDGs) # 6 and 12.